Management of Storm Water Quality in Urban Areas - Sarukkalige, Priyantha Ranjan (IJEAT, 2012)
The main aim of this paper is to highlight the importance of the management of storm water quality in enhancing their activities to improve regional water quality. The procedure on developing storm water management strategies consists of reviewing existing water quality data, identifying water quality issues and developing a decision making tool for the officers, managers and decision makers. It was found that land use activities are the main factor affecting the water quality. Therefore, activities, sources and pollutants related to different land use types including residential, industrial, agricultural and commercial are given high importance during the study. Different management groups and authorities were analyzed in order to understand the associated management framework and issues. The issues identified were used in preparing the decision making tool. Variables associated with the defined “value versus threat” decision making tool are obtained from the intensive literature review. The main recommendations provided for improvement of water quality, include non-structural, structural and management controls.